Implementasi Sistem Gateway Discovery pada Wireless Sensor Network (WSN) Berbasis Modul Komunikasi LoRa - Alfian Rizky Susanto; Adhitya Bhawiyuga; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless Sensor Network (WSN) is a network of several nodes that do sensing and can control the environment, can contain interactions between humans and computers and the state of the environment. WSN has several components that are used for environmental monitoring such as sensor nodes and gateways to collect sensor data. Both components communicate with wireless technology intermediaries. One of the wireless technologies is LoRa. LoRa is a low-power wireless technology that uses the radio spectrum. LoRa characteristics that can accommodate long distances and low power consumption, are suitable to be applied to the WSN. But there are shortcomings in the implementation of LoRa, namely the absence of a gateway discovery system in LoRa. From this explanation, this research focuses on creating gateway discovery system to overcome these shortcomings. The performance test results show that the system built can function up to a distance of 1000 meters. At the maximum distance of performance testing, namely 1000 meters, the association time value is 354.4 milliseconds, unicast loss is 6% and broadcast loss is 20%. This has an impact on the performance of gateway discovery system because increase value of these parameters, the system performance will get worse.